2020
DOI: 10.1038/s10038-020-0730-1
|View full text |Cite
|
Sign up to set email alerts
|

Transmission characteristics of SMN from 227 spinal muscular atrophy core families in China

Abstract: To define the relationship between the survival motor neuron 1 gene (SMN1) and SMN2, and explore the variability of these two genes within the generations, SMN1 and SMN2 copy numbers were determined for 227 SMA families. The association analysis indicated that there was a negative correlation between the copy number of SMN1 and SMN2 (Spearman = −0.472, P < 0.001) in 227 SMA children and 454 of their parents. The average SMN copies from father and mother in each SMA family were used to represent the copy number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Besides, current data illustrated that the variation of SMN copy number passed through inheritance; thus, the SMA severity could be predicted from the parents' generation to some extent. Correspondingly, the mentioned study has supported the same by assessing two generations of Japanese families (Cao et al, 2020). However, in the current study, the negative correlation between SMN1 and SMN2 copy numbers seemed to be less linear, indicating there might be individuals with two or more SMN2 copies in one allele, or it has occurred due to the genetic structure varieties throughout ethnicities.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Besides, current data illustrated that the variation of SMN copy number passed through inheritance; thus, the SMA severity could be predicted from the parents' generation to some extent. Correspondingly, the mentioned study has supported the same by assessing two generations of Japanese families (Cao et al, 2020). However, in the current study, the negative correlation between SMN1 and SMN2 copy numbers seemed to be less linear, indicating there might be individuals with two or more SMN2 copies in one allele, or it has occurred due to the genetic structure varieties throughout ethnicities.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, in the case of SMN copies, there was consistency between patients and their parents regardless of SMA type. In research conducted by Cao, Y. et al data showed that in 27 PKU core families, the distribution of both the copy number of SMN1 and SMN2 had no signi cant difference between the PKU children and their parents (P = 0.607 for SMN1 and P = 0.326 for SMN2) (Cao et al, 2020). Their result indicated that there is a positive correlation between patients and their parents in case of both SMN1 and SMN2 copy numbers (Spearman = 0.75 P < 0.001 for SMN1; Spearman = 0.696, P < 0.001 for SMN2).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, a recent study reported that the copy number of SMN genes may determine the pathological type of SMA patients. Cao et al [ 11 ] found that in different copy numbers of SMN2 , the distribution of type I and type 2/3 was significantly different ( P < 0.001): when the copy number of SMN2 in parents was 1, 75% of SMA progenies were type 1 and 25% were type 2/3. However, when the parents carried three copies of SMN2 , their SMA progenies were all 2/3 type.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent study reported that the copy number of SMN genes may determine the pathological type of SMA patients. Cao et al [11] found that in different copy numbers of SMN2, the distribution of type I and type 2/3 was signi cantly different (P < 0.001): when the copy number of SMN2 in parents was 1, 75% of SMA progenies were type 1 and 25% were type 2/3. However, when the parents carried three copies of SMN2, their SMA progenies were all 2/3 type.…”
Section: Introductionmentioning
confidence: 99%